Struktur Percakapan Host Utama Dalam Talk Show Oshareizumu - Elsy fitriyany; Yanti Hidayati; Andi Abd Khaliq Syukur (IZUMI, 2024)
This research analyzes the conversational structure of the main host in the talk show "Oshareizumu." The primary focus is on the speaking style and interaction strategies used by the main host, Ueda. A pragmatic approach is employed as the theoretical framework, referencing the theories of Yule (2014) and Lidia Tanaka (2014). This study identifies three instances of pauses, three instances of overlap, and one hundred and nineteen occurrences of backchannel or aizuchi. Ueda's intensive and active speaking style demonstrates a high level of involvement in interactions. The results show that Ueda performs his role effectively, as evidenced by a conversational structure with minimal pauses and overlaps, extensive use of backchannel, and an intensive speaking style. These findings suggest that Ueda's contributions significantly enhance the attractiveness of the talk show. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor